On the relationship between reachability problems in timed and counter automata - Haase, C; Ouaknine, J; Worrell, J (2012)
This paper establishes a relationship between reachability problems in timed automata and space-bounded counter automata. We show that reachability in timed automata with three or more clocks is naturally logarithmic-space interreducible with reachability in space-bounded counter automata with two counters. We moreover show the logarithmic-space equivalence of reachability in two-clock timed automata and space-bounded one-counter automata. This last reduction provides new insight into two problems whose precise computational complexity have independently been identified as open. © 2012 Springer-Verlag.